2011
DOI: 10.1177/0960327111417910
|View full text |Cite
|
Sign up to set email alerts
|

Carbendazim combined with imazalil or cypermethrin potentiate DNA damage in hepatocytes of mice

Abstract: Traces of pesticides imazalil, cypermethrin and carbendazim are detected in plants used for human consumption. To explore whether their application in oral combinations will induce DNA breaks in hepatocytes, a subchronic in vivo experiment was performed in Swiss mice. Doses of 10 mg kg(-1) of imazalil (im) and cypermethrin (cy), and 20 mg kg(-1) of carbendazim (car) and their combinations (im, 10 mg kg(-1) + cy, 10 mg kg(-1); im, 10 mg kg(-1) + car, 20 mg kg(-1); car, 20 mg kg(-1) + cy, 10 mg kg(-1)) were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…Similarly, Dikic et al. [87] in their study have reported hepatic DNA breakage in mice treated with CYP at a sub-lethal dose as used in our study. Treatment with EC however, drastically reduced the formation of 8-NO 2 Gua in the rats, reflecting the ability of the flavonoid in preventing nitrosative damage to nucleic acids, especially as EC is an effective inhibitor of iNOS [29].…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, Dikic et al. [87] in their study have reported hepatic DNA breakage in mice treated with CYP at a sub-lethal dose as used in our study. Treatment with EC however, drastically reduced the formation of 8-NO 2 Gua in the rats, reflecting the ability of the flavonoid in preventing nitrosative damage to nucleic acids, especially as EC is an effective inhibitor of iNOS [29].…”
Section: Discussionsupporting
confidence: 78%
“…Hepatotoxic properties of cypermethrin have already been described in mice (44). The major fi nding of our experiment is that beta-cyfluthrin has a greater hepatotoxic potential than cypermethrin.…”
Section: Figure 1a To 1v Histoarchitecture Of Wistar Rat Liver; (A) Cmentioning
confidence: 49%
“…However, it was shown their antagonistic effect in combination mixture with less pronounced DNA damage [ 50 ]. The mixture of imazalil, cypermethrin and carbendazim caused DNA damage in hepatocytes evaluated by comet assay due to synergistic effects; in this case, carbendazim potentiated the effects of imazalil and cypermethrin [ 51 ].…”
Section: Discussionmentioning
confidence: 99%